Molecular Characterization, Phylogenetic, Expression, and Protective Immunity Analysis of OmpF, a Promising Candidate Immunogen Against Yersinia ruckeri Infection in Channel Catfish - Wang, Erlong; Qin, Zhenyang; Yu, Zehui; Ai, Xiaohui; Wang, Kaiyu; Yang, Qian; Liu, Tao; Chen, Defang; Geng, Yi; Huang, Xiaoli; Ouyang, Ping; Lai, Weimin (Frontiers in Immunology, 2018)
Outer membrane porins, as the major components of Gram-negative bacterial membrane proteins, have been proved to be involved in interactions with the host immune system and potent protective antigen candidates against bacteria infection in fish. Outer membrane porins F (OmpF) is one of the major porins of Yersinia ruckeri (Y. ruckeri), the causative agent of enteric red mouth disease of salmonid and non-salmonid fish. In the present study, the molecular characterization and phylogenetic analysis of OmpF gene was identified, heterogenous expression, immunogenicity and protective immunity of OmpF were systemically evaluated as a subunit vaccine for channel catfish against Y. ruckeri infection. The results showed that OmpF gene was evidenced highly conserved among 15 known Yersinia species based on the analysis of conserved motifs, sequences alignment and phylogenetic tree, and was subjected to negative/purifying selection with global dN/dS ratios value of 0.649 throughout the evolution. Besides, OmpF was identified to have immunogenicity by western blotting and was verified to locate on the surface of Y. ruckeri using cell surface staining and indirect immunofluorescence assays. Moreover, recombinant OmpF (rtOmpF) as subunit vaccine injected with commercial adjuvant ISA763 significantly enhanced the immune response by increasing serum antibody titers, lysozyme activity, complement C3 activity, total protein content, SOD activity, immune-related genes expression in head kidney and spleen, and survival percent of channel catfish against Y. ruckeri infection. Thus, our present results not only enriched the information of molecular characterization and phylogenetics of OmpF, but also demonstrated that OmpF hold promise used as potential antigen against Y. ruckeri infection in fish.